2018
DOI: 10.15295/bmij.v6i3.348
|View full text |Cite
|
Sign up to set email alerts
|

Örgütsel Muhalefeti̇n Ki̇şi̇sel Değerler Ve Psi̇koloji̇k İyi̇ Oluş İle İli̇şki̇ni̇n İncelenmesi̇

Abstract: The main purpose of the study is to examine the relationship of organizational dissent with personal values and psychological well-being. The research data were collected from 272 employees of various public institutions in the province of Kocaeli through a questionnaire. Relationships between variables were analyzed using structural equation model. According to results of the study; self-enhancement has a positive effect on displaced dissent; openness to change has a positive effect on articulated dissent and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In the literature review conducted by the researcher, there is no study examining the relationship between job performance and organizational opposition. However, it has been found that it is associated with various variables such as organizational opposition and climate perception (Karalar, & Usta-Kara, 2020), personal values and psychological well-being (Acaray, 2018), five-factor personality model (Ökten, & Cenkçi, 2013), organizational power games (Korucuoğlu, & Şentürk, 2018) organizational cynicism and organizational commitment (Yıldız 2013) critical thinking dispositions (Püsküllüoğlu, & Altınkurt, 2018) and perception of professional self-efficacy (Bakan, et al 2017). The concept of organizational opposition has a very important place in the formation and development of democracy within the organization.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature review conducted by the researcher, there is no study examining the relationship between job performance and organizational opposition. However, it has been found that it is associated with various variables such as organizational opposition and climate perception (Karalar, & Usta-Kara, 2020), personal values and psychological well-being (Acaray, 2018), five-factor personality model (Ökten, & Cenkçi, 2013), organizational power games (Korucuoğlu, & Şentürk, 2018) organizational cynicism and organizational commitment (Yıldız 2013) critical thinking dispositions (Püsküllüoğlu, & Altınkurt, 2018) and perception of professional self-efficacy (Bakan, et al 2017). The concept of organizational opposition has a very important place in the formation and development of democracy within the organization.…”
Section: Discussionmentioning
confidence: 99%
“…It can also be seen that different power groupings have been made based on the sources of power defined by Weber (French, Raven & Cartwright, 1959;Yukl & Chavez, 2002). In literature, there have been studies about the concepts related to the use of power sources in school organizations such as organizational silence and motivation (Deviren, 2019), organizational commitment (Bağcı & Bursalı, 2011), organizational citizenship behavior (Çınar & Özen, 2019;Karaman, Yücel & Dönder, 2008;Uzun, 2019), organizational cynicism (Acaray, 2018;Balay, Kaya & Cülha, 2013), organization environment (Ayık & Diş, 2016, Koşar & Çalık, 2011 and job satisfaction (Yılmaz & Altınkurt, 2012). What makes this study different from the ones mentioned above is that the sources of power used by school administrators will be examined closely within the scope of Weber's typology of power.…”
Section: Introductionmentioning
confidence: 99%